Pricing strategy of traceable agricultural supply chain decisions considering retailer's overconfidence with government subsidy - Chongfeng Lan; Yaru Lan; Shengde Liu (Alexandria Engineering Journal)
This study examines pricing strategies within a two-tier traceable agricultural product supply chain, encompassing both the retailer and the supplier. A pricing decision model was developed to evaluate scenarios characterized by the retailer's overconfidence as well as those devoid of such bias. This research employs Stackelberg game theory to investigate the impact of government subsidies, retailer overconfidence and consumer preferences for traceability on the performance of supply chain participants and the overall system. Our analysis derives the following findings: (i) retailer overconfidence strengthens their commitment to traceability, thereby enhancing the overall efficacy of the supply chain. (ii) Additionally, consumer demand for traceability incentivizes retailers to intensify their traceability initiatives, aligning with consumer purchasing expectations. (iii) The pricing decisions made by retailers are influenced by their overconfidence, consumer preferences for traceability, and the presence of government subsidies. (vi) The study also shows that retailer overconfidence and customer demand for traceability have the most effects on supply chain performance when decision-making is centralized.